“Too Long, in Two Colors”. On Dichotomy in the Poetry of Jacek Bierezin - Czapiewski, Oskar (Contrasts in humanities: literature, language, culture, 2023)
This article focuses on the interpretation of the work of Polish contemporary poet Jacek Bierezin (1947-1993), one of the main representatives of the New Wave (Nowa Fala) formation. The author points out the dichotomous poetics present in Jacek Bierezin’s poems using biographical motifs and emphasizing the influence of the author’s biography on his work. As literature on the subject the author uses the collection Linia życia (1999) published after Jacek Bierezin’s death as well as the volume Obudź mnie ze sobą! (2000), also published posthumously. Using the works of other researchers, the author constructs conclusions on the bordering features of Jacek Bierezin’s poetic works.